A Multiion, Flux‐Corrected Transport Based Hydrodynamic Model for the Plasmasphere Refilling Problem. Issue 1 (13th January 2020) - Chatterjee, K.; Schunk, R. W.
Abstract: The objective of this paper is the application of a newly developed flux‐corrected transport based hydrodynamic solution methodology to the plasmasphere refilling problem following a geomagnetic storm. The flux‐corrected transport method is extremely well‐suited to the solution of nonlinear partial differential equations with shocks and discontinuities. In this solution methodology, every ion species is modeled as two separate fluids originating from the northern and southern hemispheres. We present refilling results that include three ion (H +, He +, and O + ) species and two neutrals (H and O). We believe that with additional modifications, the model can be adapted to the solution of other ionosphere‐magnetosphere coupling problems. Plain Language Summary: The paper applies a newly developed multispecies hydrodynamic model to the plasmasphere refilling problem following geomagnetic storms. We believe that with additional development, the model can be applied to other ionosphere‐magnetosphere coupling problems. Key Points: Developed a hydrodynamic model for the plasmasphere refilling problem following geomagnetic storms The model is based on the well‐known flux‐corrected transport method The model is applied to the plasmasphere refilling problem for three ion species and two neutrals along the L = 4 line